ASSESSING THE SENSITIVITY OF NECK CIRCUMFERENCE AS A PREDICTOR OF CENTRAL OBESITY IN ADULT HYPERTENSIVE PATIENTS. (April 2021) - Patil, Mansi; Patil, Vishal; Schlaich, Markus; Lambert, Gavin
Abstract: Objective: Waist circumference has been used till now for determining central obesity which is found to be considerably variable over a short period of time. Neck circumference on the other hand is reliable and does not show short term variability. The objective of the study was to determine the cut-off values of neck circumference as a predictor of central obesity in adult hypertensive patients. Design and method: A cross-sectional study was carried out on 500hypertensive patients under treatment to assess the correlation of neck circumference and waist circumference by applying the pairwise correlation coefficient. Height, weight and waist circumference were measured using the NHANES standard procedures. BMI was calculated from the data. ROC curve analysis was performed and Youden index was calculated. Neck circumference yielding the maximum Youden Index was considered as the cut-off for central obesity. Results: Neck circumference was found to be significantly associated with waist circumference in both females and males with b-coefficients of 1.06 (95% CI: 0.87, 1.17) and 0.71 (95% CI:0.51, 0.79), respectively. After applying ROC analysis, neck circumferences more than equal to 34 cms in females and more than equal to 38 cms in males was determined as the best cut-off to predict central obesity. When compared with BMI, AUC of NC (0.75; 95% CI: 0.73–0.78) for predicting central obesity was higher than AUC of BMI (0.74; 95% CI: 0.72–0.77). Figure. No caption available. Conclusions: Neck circumference could be considered as an alternative for screening for central obesity in hypertensive patients. Neck circumference can be used as a screening tool for pregnant women or for patients suffering from ascites and does not require removal of clothing. The procedure for measurement of neck circumference requires minimal training with lesser scope of error in measurement. Position of measurement (supine/prone/standing), meal consumption or respiration does not hamper the measurement and can be measured in bed-ridden patients also.